Efficacy and safety of telitacicept in the treatment of IgA nephropathy: a single-center, real-world study - Tao, Lin; Zhang, Xiaoling; Niu, Xiaoge; Liu, Gailing; Jiao, Xiaojing; Shao, Fengmin; Cao, Huixia (Frontiers in Pharmacology, 2025)
AimTo evaluate the efficacy and safety of Telitacicept in patients with IgA nephropathy. Telitacicept is a fusion protein that inhibits B-cell activating factor (BAFF) and a proliferation-inducing ligand (APRIL), thereby modulating B-cell activation and survival.MethodsA single-center, retrospective analysis of data from 24 patients with IgA nephropathy who received telitacicept 160 mg per week, with a minimum continuous treatment of 12 weeks, from August 2022 to January 2024. Patients were categorized by treatment regimen: telitacicept monotherapy (Group A, n = 8), telitacicept combined with low-dose corticosteroids (prednisone 0.3–0.5 mg/kg/day) (Group B, n = 8), and telitacicept combined with full-dose corticosteroids or corticosteroids plus other immunosuppressants (Group C, n = 8). Clinical data before treatment (baseline) and after 4, 12, and 24 weeks of treatment were analyzed and safety assessed.ResultsMean serum creatinine and eGFR levels remained stable in all three groups. After 12 weeks and 24 weeks of treatment, patients in all three groups showed a significant decrease in 24 h proteinuria from baseline (P < 0.05). Treatment with Telitacicept was generally well-tolerated, with no serious adverse events related to the study drug. Complete remission was achieved in 4 patients (16.7%), partial remission in 15 patients (62.5%), and no response in 5 patients (20.8%).ConclusionTelitacicept monotherapy is safe and effective, and combination with corticosteroids and immunosuppressants may improve the remission rate in patients with better baseline renal function, but modestly increases the risk of adverse reactions.